Tasavvuf geleneğinin Osmanlı siyasî düşüncesinde tezâhürü - Öztürk, Özkan (My University, 2014)
Soyadı: Özkan ÖZTÜRK Felsefe ve Din Bilimleri Felsefe ve Din Bilimleri Bilim Dalı Prof. Dr. İsmail KARA Tez Türü ve Tarihi: Doktora-Mart 2014 set Felsefesi, Osmanlı Siyâsî Düşüncesi, Bursevî, Sarı Abdullah Efendi, İbn Arabî, Vahdet-i Vücûd, Siyâset, Ricâlu’l-Gayb

TASAVVUF GELENEĞİNİN OSMANLI SİYASÎ DÜŞÜNCESİNDE TEZÂHÜRÜ İbn Arabî düşüncesinin siyâsetle ilişkisi özellikle İsmail Hakkı Bursevî and Sarı Abdullah Efendi olmak üzere Osmanlı sûfileri tarafından yeniden yorumlanmıştır. Onlar siyaset alanında İbnü’l-Arabî’nin önemli takipçileri olmuşlardır. Varlık alanında, içinde yaşanılan dünyanın dışında, akılla kavranılması mümkün olan siyâsî bir âlem düzeni tasarlamışlardır. Bu düşünce temelde dört varlık mertebesi için geçerlidir. Bu mertebelerin en üstü ilâhî isimler mertebesidir. Bu mertebe diğer mertebeler için de belirleyicidir. Diğer mertebeler misâl, mülk ve insân âlemleridir. Bütün âlemlerin yöneticisi kutub, mülk âleminin yöneticisi sultan ve insânî âlemin yöneticisi ise insânî rûhtur. Bu çalışmada, varlık mertebeleri ve bunların birbirleri ile olan siyâsî irtibatları incelenmiştir. İlâhî isimler teorisi ve vahdet-i vücûd düşüncesinden hareket eden bu anlayışta insân-ı kâmil, imâmet, hilâfet, kutbiyyet, saltanât, mülk, adâlet, salâh ve fesad gibi kavramların siyasî düşüncedeki konumları belirtilmiştir. Bu çalışmada, sûfî düşünürlerin siyâsî fikirlerinde vahdet-i vücûd hikmetinin nasıl özümsendiği ve bu geleneğin Osmanlı siyâsî düşüncesine intikali “ilâhî isimler teorisi” ışığında incelenmiştir. Bu etki Osmanlı Devlet hiyerarşisinde ve siyâsî uygulamalarda açıkça görülmektedir. Name and Surname: Özkan ÖZTÜRK Field: Department of Philosophy and Religious Studies Programme International: Philosophy and Religious Studies Supervisor: Prof. Dr. İsmail KARA Degree Awarded and Date: Master-March 2014 Political Philosophy, Otoman Political Thought, Bursevî, Sarı Abdullah Efendi, Ibn al-Arabî, Wahdat al-Wujud, Politics, Ricâlu’l-Gayb ABSTRACT THE REFLECTİON OF SUFİC TRADİTİON İN THE OTTOMAN POLİTİCAL THOUGHT The thought of Ibn al-Arabi and its relation with politics has been reviewed by Ottoman Sufis, notably Ismail Hakki Bursevi and Sari Abdullah Efendi. They were significant followers of Ibn al-Arabi in the field of politics. They designed an order of a Political Universe, which is out of the present world but possible to fathom through mind, within the compass of existence. This concept of theirs is essentially based on four stages of existence. At the top of these, the stage of Divine Names stands. The stage of Divine Names also designates the other stages of existence. The other stages are universe of misal (non-material world), mulk (material world/ external world), insan (the world of human). The governor of all universe is kutb (the perfect human being-the greatest master), the governor of material world/ external world is sultan and the governor of the human world is human spirit. In this study, the stages of existence and their political engagements with each other has been probed. In this mentality, abided by the theory of Divine Names and the comprehension of wahdat al-wujud, the position of concepts such as insan-i kamil (perfect human being), imamet (Imamate), hilafet (Caliphate), kutbiyyet, sultanate, mulk (external world), adalet (Justice), salah (righteousness), fesad (unrighteousness) has been manifested. In this study, it has been analysed that how the profundity of wahdat al-wujud is imbibed by the sufi philosophers. And the way this precedent was transferred by heritage to the Ottoman political thought under the guidance of Divine Names Theory. This impact is obviously seen in the hierarchy of Ottoman State and political practices.
Keywords: Felsefe; Osmanlı İmparatorluğu; Osmanlı Siyâsî Düşüncesi; Siyâset Felsefesi; Sufizm_Sufiler__Bursevî_ Sarı Abdullah Efendi_ İbn Arabi; Tasavvuf_îVahdet-i Vücûd, Siyâset, Ricâlu’l-Gayb